2017
DOI: 10.5234/cnpt.8.7
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in drinking water may be negatively associated with depressive temperament in the nonclinical population

Abstract: Purpose: Recently, we reported that lithium levels in drinking water were significantly and positively associated with hyperthymic temperament scores, whereas latitude was significantly and negatively associated with the scores, suggesting that lithium in drinking water may positively maintain hyperthymic temperament and that latitude may negatively maintain it. In the present study, from the viewpoint of psychopharmacology, we investigated the other 4 affective temperaments in reference to lithium in drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this necessitates further clinical studies to confirm the aforementioned findings. For example, in the association between suicide rate and lithium in drinking water, we performed clinical studies [2,3] to directly confirm the indirect evidence from epidemiological studies [27][28][29][30] although we could not perform RCTs for that field.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised controlled trial, microdoses of lithium were shown to have positive mood effects when provided as an oral supplement (Schrauzer and de Vroey, 1994). Furthermore, higher lithium levels in drinking water significantly reduced the prevalence of depressive temperament in Japan (Ishii et al, 2018). A similar systematic review and meta-analyses found lithium in drinking water were dose-dependently associated with reduced suicide mortality (Barjasteh-Askari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study by König et al (2017) showed that suicide rates were lower (9.99/100 000) in high lithium-districts in comparison to other districts (12.5/100 000) in Chile in the period 2000–2009 ( P < 0.001). In a study, Ishii et al (2017) demonstrated that lithium concentrations in potable water were significantly and negatively correlated with depressive mood grades, but not with sunshine, temperature, or latitude in five cities of Japan. Another study in five districts of Japan reported that the latitude and ambient temperature were significantly correlated with hyperthymic mood, but not sunshine (Inoue et al , 2015).…”
Section: Discussionmentioning
confidence: 99%